Effects of Entrepreneurial Family Background on Students’ Entrepreneurial Intention: A Study at Universiti Malaysia Kelantan, Jeli Campus and Universiti Utara Malaysia, Sintok Campus - Mohamed Khadri, Nurul Azwa; Wei, Ewe Khai; Abu Bakar, Abu Suffian; Sidek, Syamsuriana; Hasbolah, Hazrina; Nik Muhammad, Nik Maheran (International Journal of Criminology and Sociology, 2022)
The purpose of this study is to analyse the determinants of students’ intention towards entrepreneurship. This study used the Theory of Planned Behaviour (TPB) represented by three variables (attitudes, subjective norms and perceived behaviour control) and family background as the determinant that could influence students’ intention to become an entrepreneur. A total sample of 489 university students from Universiti Malaysia Kelantan, Jeli Campus and Universiti Utara Malaysia, Sintok Campus was used in the analysis. Results from the study indicated that perceived behaviour control had a significant relationship towards students’ intention to become an entrepreneur. At the same time, attitudes and subjective norms were not significantly related to students’ intention towards entrepreneurship. This study also examined the impact of entrepreneurial family background as a mediating factor in the relationships between attitudes, subjective norms and perceived behaviour control towards students’ entrepreneurial intentions. The findings can contribute to new knowledge in the field of the family business and have practical implications in entrepreneurship education for university students.